Allergic diseases, drug adverse reactions and total immunoglobulin E levels in lupus erythematosus patients - Anna Wozniacka; Anna Sysa-Jedrzejowska; Ewa Robak; Zbigniew Samochocki; Malgorzata Zak-Prelich (Mediators of Inflammation)
Background: The association of allergic diseases, drug adverse reactions and elevated total immunoglobulin E (IgE) concentration in systemic lupus erythematosus patients remains controversial. The aim of the study was to investigate the prevalence of those features in active and inactive systemic lupus erythematosus patients, and in the control group as well.